A survey on osteogenic effect of collagen-membrane derived from Rutilus kutum swim bladder in rat calvaria - Farid Bahrizadeh; Hamidreza Azimi Lisar; Noushin Jalayer Naderi (Wolters Kluwer Medknow Publications, 2021)
Background: The collagen membrane which obtained from bovine pericardium and human skin in Guided Bone Regeneration (GBR) is costly and may even cause transmission of diseases. Replacing conventional collagen membranes with a more easily accessible and cheaper ones will have economic benefits. The aim was to determine the osteogenic effect of collagen-membrane derived from Rutilus kutum swim bladder on rat calvaria. Materials and Methods: The study was experimental. Thirty-six male albino rats of the Wistar strain were included in the study. The 5 mm surgical defects were created on calvarias and filled with allograft bone material and covered by R. kutum swim bladder (Group I), bovine derived pericardial membrane (Group II) and without membrane cover (Group III).The specimen were euthanized after 3, 5 and 8 weeks. The surrounding connective tissue was evaluated in term of osseous formation. Kruskal-Wallis, Univariant analysis of variance, and post hoc tests were used for statistical analysis. The P < 0.05 was considered statistically significant. Results: A significant differences between groups in terms of osseous formation (P = 0.001) was noted. The difference of osseous formation was significantly higher in 5 and 8 weeks than 3 weeks after operation in all groups (P = 0.03 and P = 0.006, respectively). The osseous formation in Group I and II were significantly higher than Group III (P = 0.023 and P = 0.001). Conclusion: The R. kutum swim bladder had osteogenic effect on rat calvaria. R. kutum swim bladder can be a new source in natural derived collagen membrane in GBR.